Educational Activities for Students and Citizens Supporting the One-Health Approach on Antimicrobial Resistance - Massimiliano Marvasi; Lilliam Casillas; Alberto Vassallo; Diane Purchase (MDPI AG, 2021)
Antibiotic resistance is one of the biggest threats to global health, food security and development. Urgent action is needed at all levels of society to reduce the impact and spread of antibiotic resistance. For a more sustaining approach, education in children, college students, citizens and caregivers are essential. The One-Heath approach is a collaborative, multisectoral and transdisciplinary strategy in which, no single organizations or sector can address the issue of antimicrobial resistance at the human-environment interface alone. Within this strategy, education plays a central role. In this scoping review, we highlighted a range of learning activities on antibiotic resistance as part of the One-Health approach. In particular, those applications that can be introduced to a wide audience to help arrest the current crisis for the next generation. The review identifies a high number of teaching opportunities: board and role-play games, round tables, musicals, e-learning and environmental experiments to couple with more curricula and formal education to inform a diverse group of audiences.